Effect of Sample Storage at 2-8°C for 24 Hours on Reticulocyte Count Determined by Manual Method: Effect of Sample Storage on Reticulocyte Count - Khalid, Abeeha; Ghazanfar, Masuma; Mustafa, Ammara; Bashir, Robish; Abdal, Hassan (Pakistan Journal of Health Sciences, 2025)
Reticulocytes are immature red blood cells that contain residual RNA and ribosomes but no nucleus. Reticulocytes count is a haematological test that assists in assessing bone marrow activity. It can be determined by manual and flow cytometric method. Reticulocytes mature in vitro within six hours of sample collection; hence the sample should be processed within this time frame for accurate results. Objective: To determine the difference in reticulocyte count between a fresh sample and a sample stored for 24 hours at 2-8°C by manual method. Methods: This quasi-experimental study included a total of 220 EDTA-anticoagulated blood samples submitted to the Hematology Department of Allama Iqbal Medical College/Jinnah Hospital, Lahore, from June 12, 2024, to December 18, 2024, for reticulocyte count analysis using non-probability consecutive sampling technique. Each sample was processed using brilliant cresyl blue stain, within one hour of collection and reported two times: within 6 hours of sample collection and after a period of 24 hours of storage. Results: The manual reticulocyte count showed a significant difference between freshly prepared slides and those stored for 24 hours. Mean reticulocyte count at 6 hours was 2.99 ± 0.09, while after 24 hours, it decreased to 2.41 ± 0.10, resulting in a mean difference of 0.58 ± 0.16. Conclusions: In regions where automated methods are not available, performing a reticulocyte count manually on a fresh sample can significantly contribute to improving healthcare quality. This simple yet essential test is crucial for diagnosing and managing various clinical conditions effectively.